Economic Potential Based on an Engineering Analysis of Jackfruit Waste as Food Biopreservative Packaging to Alleviate Poverty in Lombok Barat, Nusa Tenggara Barat - Saputra, Doni (Faculty of Social Science, Universitas Negeri Semarang, 2017)
Rate of poverty and unemployment in Lombok Barat shows high precentage 17.11 % of total population and 3.35% of total labor-force. Seventy percent of poverty in Lombok Barat is a farmer. That was caused by their incapability to give additional value to their product. Whereas, Lombok Barat is the biggest produser of jackfruit in NTB which its waste can be made as biopreservative packaging that is incorporated with clove oil as antimirobial which can be economically benefits to alleviate poverty and unemployment. Economics potential of jackfuit waste packaging was used Cooperative Economics Sytem which is the owner of company based on Kelompok Tani in each sub-district in Lombok Barat. Value of company’s feasibility and profitability was conducted with Engineering Economics Analysis. The result of analysis shows that BEP value 42,06% and profit per year Rp. 124,847,815,400.00 with capacity 4 tons/day, ROI 76.04% and POT 1.31 year. The analysis also shows the product’s price is Rp. 25,000.00 which is still competitive with conventional’s price. It can provide a new job vocancies which is estimated reduce poverty rate and unemployment rate 1.0% and 0.23%, respectively.